2003
DOI: 10.3354/meps256063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enteromorpha intestinalis mats on near-bed currents and sediment dynamics: flume studies

Abstract: The influence of the macroalgal mats of Enteromorpha intestinalis on near-bed current velocities and sediment dynamics was quantified by placing relatively undisturbed cored sediments in annular flumes. Density-dependent relationships were established for E. intestinalis densities; these ranged from 10 to 60% cover when air-exposed (biomass of 4 to 40 g ash-free dry wt m-2) and in comparison with bare sediment (0% cover). There was a significant increase in friction drag with increasing E. intestinalis biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
(10 reference statements)
1
25
0
2
Order By: Relevance
“…Gambi et al 1990). For example, Romano et al (2003) found that a mat of Enteromorpha intestinalis reduced current velocities by 10 to 56% and sediment erosion by 60 to 90%. Ampelisca abdita tubes covered essentially 100% of the bottom at Sites 2 and 4 (amphipod densities of 31 000 and 19 000 m -2 , Table 2).…”
Section: Sediment Erosionmentioning
confidence: 99%
“…Gambi et al 1990). For example, Romano et al (2003) found that a mat of Enteromorpha intestinalis reduced current velocities by 10 to 56% and sediment erosion by 60 to 90%. Ampelisca abdita tubes covered essentially 100% of the bottom at Sites 2 and 4 (amphipod densities of 31 000 and 19 000 m -2 , Table 2).…”
Section: Sediment Erosionmentioning
confidence: 99%
“…17 Δ could be enhanced in a similar manner by mixing of water from Ruppia or macroalgae dominated areas during nighttime convection-during the daytime, wind-dominated mixing tended to homogenize pond water along the wind fetch, but allowed large gradients in oxygen concentration (differences in O2 saturation state of >100 to 200% between adjacent bare sediments and macroalgae or Ruppia dominated patches) and 17 Δ (differences of 20 to 50 per meg between patches). While it seems unlikely that such heterogeneity would persist for long after O2 became undersaturated (the O2 residence time with respect to gas exchange is 6 hours at night), in the absence of strong lateral mixing, areas with extensive Ruppia and macroalgal mats likely had much slower air-water exchange than in water over open sediments because of turbulence reduction by the vegetation (Koch and Gust 1999, Romano et al 2003, Nepf and Ghisalberti 2008. Either dissolution of bubbles or enhanced convective mixing would likely be heterogeneous in space and time and could slow the expected overall rate of 17 Δ decrease.…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…Species of Ulva are primarily marine taxa found in saline and salty waters , Haroon et al 1999, Lee 1999, Kirchhoff and Pflugmacher 2002, Romano et al 2003, Żbikowski et al 2005), but they can also proliferate in freshwater habitats. Most studies concerned with Polish examples of this group of algae examine sites located on the Baltic seashore, with only a few reports on their distribution in inland Poland (Kozłowski 1890;Raciborski 1910;Torka 1910;Wysocka 1952;Marczek 1954;Piotrowska 1961;Wilkoń-Michalska 1963;Podbielkowski 1969;Pliński 1971Pliński , 1973aKowalski 1975;Sitkowska 1999;Messyasz -in press;Messyasz and Rybak 2008).…”
Section: Introductionmentioning
confidence: 99%